Correction: A randomised survey of the quality of antibiotics and other essential medicines in Indonesia, with volume-adjusted estimates of the prevalence of substandard medicines. - Elizabeth Pisani; Ayu Rahmawati; Esti Mulatsari; Mawaddati Rahmi; William Nathanial; Yusi Anggriani; STARmeds Study Group (PLOS Global Public Health)
[This corrects the article DOI: 10.1371/journal.pgph.0003999.].